The Use of Big Data in The Oil and Gas Upstream Industry: A Comparison Between Norway And Indonesia - Syaifullah, Khalid Istiqlal (Indonesian Journal of Energy, 2019)
A study has been done to perceive the uptake and impact of Big Data in the exploration and production of oil and gas in Indonesia compared to Norway. Interviews were conducted to officials in the Ministry of Energy and Mineral Resources (MoEMR) and the state regulator, SKK Migas. In both industries, more data is being generated more than ever in exploration, production, drilling, and operations, indicating potential application of Big Data. However, approach towards data has remained classical with physical models in opposed to common Big Data approach, which is data-driven analytics. Several impacts of Big Data in both industries are highlighted, including new demand for data analysts, the need for regulations surrounding cyber-security, improvement of safety and environment (which hasn’t been considered in Indonesia), and growing need for more trust and regulations towards open data. Open data in the two industries has seen two different trajectories with Indonesia only implementing it very recently, while the NCS has seen open data drives competition since 1999. This study produced recommendations for the government of Indonesia on open data and how uptake and application of Big Data analytics in EOR could potentially increase national petroleum production to desired levels.